2003
DOI: 10.1159/000073938
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Endothelin Blockade on Early Cardiovascular Remodeling in the One-Clip-Two-Kidney Hypertension of the Rat

Abstract: Background: In models of hypertension and of renal failure, pharmacological blockade of the ETA receptor has been shown to cause some inconsistent lowering of blood pressure (BP) and lesser left ventricular hypertrophy (LVH). The effects of ETA receptor blockade (ETA-RB) on vascular remodeling and their potential relation to BP lowering, have not been clarified. Design: The experimental study in male Sprague-Dawley rats was designed to compare four experimental groups: (1) sham… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…Myocardial interstitial fi brosis was observed in the RVH group in accordance with previous results from our laboratory 8 and other researchers 17,18 . This component of cardiac remodeling would be the result of both humoral fi broblast stimulation leading increased collagen synthesis 17,19,20 and cellular necrosis 21 .…”
Section: Discussionsupporting
confidence: 91%
“…Myocardial interstitial fi brosis was observed in the RVH group in accordance with previous results from our laboratory 8 and other researchers 17,18 . This component of cardiac remodeling would be the result of both humoral fi broblast stimulation leading increased collagen synthesis 17,19,20 and cellular necrosis 21 .…”
Section: Discussionsupporting
confidence: 91%
“…Thus, beta-blocker treatment does seem to directly interfere with the amount of connective tissue in the heart, not only by reducing sympathetic activity but also by reducing the release of renin, plasma renin concentration, and thus the expression of cardiac angiotensin II (Varagic et al 2012). The increased myocardial fibrosis observed for the HS group relative to other groups was also observed in other studies that used other models of hypertension (Matsubara et al , 2006Hocher et al 1999;Saam et al 2003). The literature shows that mechanisms involved in cardiac remodeling in hypertensive animals include the stimulation of fibroblasts for collagen synthesis in response to various humoral factors (Challah et al 1995;Nicoletti et al 1996;Hocher et al 1999) and cell necrosis .…”
Section: Discussionmentioning
confidence: 56%
“…Increased synthesis and release of endothelin-1 exacerbates LV pump dysfunction in several cardiovascular diseases [74]. Moreover, endothelin-1 exposure can induce changes in fibrillar collagen synthesis and degradation pathways [75,76]. Sampling of the interstitial fluid through the microdialysis technique has demonstrated that compartmentalization of endothelin-1, similar to angiotensin II, occurs in vivo [77].…”
Section: Endothelin-1mentioning
confidence: 99%